Blood Mononuclear Cell Nitric Oxide Production and Plasma Cytokine Levels in Healthy Gabonese Children with Prior Mild or Severe Malaria - Perkins, Douglas J. (American Society for Microbiology, 1999)
Plasmodium falciparum malaria is an important cause of morbidity and mortality in children. Factors that determine the development of mild versus severe malaria are not fully understood. Since host-derived nitric oxide (NO) has antiplasmodial properties, we measured NO production and NO synthase (NOS) activity in peripheral blood mononuclear cells (PBMC) from healthy Gabonese children with a history of prior mild malaria (PMM) or prior severe malaria (PSM) caused by P. falciparum. The PMM group had significantly higher levels of NOS activity in freshly isolated PBMC and higher NO production and NOS activity in cultured PBMC. The investigation of NO-modulating cytokines (e.g., interleukin 12, gamma interferon, tumor necrosis factor alpha [TNF-α], and transforming growth factor β1) as an explanation for differing levels of NOS activity revealed that plasma levels of TNF-α were significantly higher in the PSM group. Our results suggest that NOS/ NO and TNF-α are markers for prior disease severity and important determinants of resistance to malaria.